Lipid-lowering effect of Sacha Inchi oil in adults with hypercholesterolemia and hypertriglyceridemia in 35-64 years old. AA.HH. Nueva Alianza, Chaclacayo. Lima - Gamarra Camacho, María (2019)
Objective: Determine the lipid lowering effect of the Sacha Inchi oil (Plukenetia volúbilis Linneo) administratingto people who have hypercholesterolemia and hypertriglyceridemia of 35 to 64 year old in the AA.HH. NuevaAlianza-Chaclacayo. Methods: The study is pre-experimental design of prospective longitudinal cut andexplanatory model. The group of patients was conformed by 30 people, who were determined blood samples oftotal cholesterol (CT), cholesterol (LDL), cholesterol (HDL) and triglycerides (TG). The treatment was consistedin adminitrate 45 ml of Sacha Inchi oil per day, during a month and a half, knowing that the admitted daily request(ADR) of omega 3 (w3) for a person who is 35 to 64 years old, is 1.5 % of the total heat value of the day in a dietrich in 1700 calories, according to the reminder of food realized by the participants. Results: At the end of thetreatment, the experimental group had favorable significant differences compare with the presented results at thebeginning of the intervention. These results are the decrease of the levels of total cholesterol, cholesterol LDL,triglycerides and increase of cholesterol HDL. Conclusions: In conclusion the daily ingestion of sacha inchi oil,decrease the hypercholesterolemia and hypertriglyceridemia in people of 35 to 64 years old